Analysing the morphological changes in vernacular domestic architecture of Kerala, India since 1947 - Dr B S Bhooshan and Manoj Kumar Kini
This paper discusses morphological changes in the vernacular domestic architecture in Kerala since 1947 (Independence of India from colonial rule) and identify the changes and analyses the reasons behind these changes. The study focuses on the gradual and vernacular architectural developments happened within the study region owing to several factors like social and political reforms and related, government initiated land reforms, migration to other parts of India and to foreign countries in search of better jobs and income, related economic factors, colonisation, change in technology and work expertise, change in materials, change in lifestyle, global exposure through channels and other communication system, climatological factors etc. The vernacular domestic architecture has undergone tremendous transformation owing to these factors and can be identified with specific typologies emerging. The major questions posed here are, 1. Can visual memory of Vernacular transferred to the contemporary architecture be considered vernacular or even designed vernacular? 2. What is the essence of Vernacular? Can we decipher the Diacritical mass that makes something remain vernacular and something cross the borderline? 3. Vernacular is ever evolving. Is there a stop point for a continuing vernacular construction practice? How do we define the tipping point, if any?